Covid-19 re-opening measures in the full-service restaurant industry: the impact in the word-of-mouth intention - Reich López, Christian; Terán Cázares, María Mayela; López Pérez, Jesús Fabián (UANL Facultad de Contaduría Pública y Administración, 2021)
One of the most affected industries due to COVID-19 has been full-service restaurants since several governments worldwide decided to close them temporarily as a measure to stop spreading the virus. As the re-opening happens, the priority on the factors for these restaurants’ customers to recommend others or Word-of-Mouth (WOM) seems to have changed, especially if analyzed according to demographics groups. This article shows empirical evidence of what factors in full-service restaurants influence a client’s word-of-mouth intentions before and during COVID-19, aiming the relevance of trust (TST) to be superior to other factors, such as the quality of the food (QF) itself.